2019
DOI: 10.3390/molecules24224111
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Human Gastric Cells to Oxidized Lipids Stimulates Pathways of Amino Acid Biosynthesis on a Genomic and Metabolomic Level

Abstract: The Western diet is characterized by a high consumption of heat-treated fats and oils. During deep-frying processes, vegetable oils are subjected to high temperatures which result in the formation of lipid peroxidation products. Dietary intake of oxidized vegetable oils has been associated with various biological effects, whereas knowledge about the effects of structurally-characterized lipid peroxidation products and their possible absorption into the body is scarce. This study investigates the impact of lino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…KEGG enrichment analysis revealed the relevant module enriched in the regulation of the PPAR signaling pathway, indicating a close relationship between fatty acids and hexanal content. In addition, many studies concerning the oxidation of hexanal by fatty acid, e.g., linoleic acid, have been performed [ 22 , 23 ]. Moreover, we also identified several interesting genes, including SLC27A1 , which may be a promising novel candidate gene for hexanal (which will be discussed below).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment analysis revealed the relevant module enriched in the regulation of the PPAR signaling pathway, indicating a close relationship between fatty acids and hexanal content. In addition, many studies concerning the oxidation of hexanal by fatty acid, e.g., linoleic acid, have been performed [ 22 , 23 ]. Moreover, we also identified several interesting genes, including SLC27A1 , which may be a promising novel candidate gene for hexanal (which will be discussed below).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, non-pharmacological therapy for mild hypertriglyceridemia includes lifestyle modification based on diet and physical activity [ 2 , 3 ]. In the Western diet, a lot of dishes are based on fats and vegetable oils and are prepared by the deep-frying method [ 4 ]. Frying with added oil leads to the formation of lipid peroxidation products that may modify not only fried food but also a fried medium and even influence amino acid biosynthesis pathways in human gastric cells in vitro or change gene expression [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Western diet, a lot of dishes are based on fats and vegetable oils and are prepared by the deep-frying method [ 4 ]. Frying with added oil leads to the formation of lipid peroxidation products that may modify not only fried food but also a fried medium and even influence amino acid biosynthesis pathways in human gastric cells in vitro or change gene expression [ 4 , 5 , 6 ]. Fried food consumption may be associated with cardiovascular disease risk (CVD) [ 7 ], although some authors did not observe a relationship between the consumption of fried foods and coronary heart disease (CHD) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that linoleic acid and its primary peroxidation product, 13-hydroperoxy-9Z,11Eoctadecadienoic acid , are converted into the corresponding hydroxy fatty acid, 13-hydroxy-9Z,11E-octadecadienoic acid , which is absorbed by human gastric tumor (HGT-1) cells after a six-hour incubation period [8]. Thus, and because it could be shown that lipid absorption is initiated in the stomach, HGT-1 cells were selected as a suitable model to evaluate the influence of oxidized lipids on the phospholipid composition in the current study [9,10].…”
Section: Introductionmentioning
confidence: 99%